Estudo hidroquímico das águas subterrâneas do Aquífero Furnas na região sudeste do estado de Mato Grosso - Magalhães, Aparecida de (2015)
Groundwater is a major fresh water reserve and therefore its study is of fundamental importance in relation to the qualitative and quantitative aspects, since the availability of groundwater resources for certain types of use depend on the knowledge of its characteristic hydrochemistry. The main objetctive of this study was to conduct a hydrochemical study of groundwater in the aquifer Furnas in southeastern state of Mato Grosso, with a view to classification and chemical differentiation of the aquifer. Thus it was possible to prove if the water quality is suitable for human consumption, agricultural or industrial purposes; and understand the rock-water interactions or any kind of human influence. For this, we collected water samples from twenty two deep wells in the region. The results led to the following considerations: The Aquifer Furnas is confined, has excellent conditions of storage and movement of groundwater. The phenomena of artesianismo and hydrotherapy occursinthe region, predominating mesothermal and thermal waters, although in some places the water is hyperthermal. Groundwater studied have low concentrations of dissolved salts, and good quality for agriculture and livestock. The low salinity is probably related to the occurrence of poorly soluble minerals in Furnas Formation, mainly quartz and feldspar. Of the twenty two samples analyzed for the iron ion, eight had higher concentration than the maximum permissible limit for human consumption, but all are below the maximum permissible limits for irrigation. With respect to ions, the most common anion is bicarbonate and the cation is magnesium, which shows the litochemical control by rocks of the Furnas Formation. The dominant chemical types, allowed to classify water samples in the region as calcic or magnesian bicarbonate waters, and the occurrence of three wells with type bicarbonate sodic waters. The main type of water observed in the region was magnesian bicarbonate.